The Dual Role of Career Women in Strengthening Family Resilience: A Study in Tulung District, Klaten Regency - Muhdi Muhdi; Fairuz Sabiq; Lila Pangestu Hadiningrum; Diana Zuhroh (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Advancements in science and technology have reshaped societal perspectives, leading to significant social changes, including expanded career opportunities for women. As wives and mothers increasingly enter the workforce, their dual roles influence family resilience. This study examines the role of career women in supporting family resilience in Tulung District, Klaten Regency. Using a field research approach, data were collected through observation, interviews, and documentation, then analyzed using the Milles Huberman interactive analysis method. Findings reveal that women in Tulung District engage in diverse professions while balancing responsibilities in both domestic and public spheres. Their ability to maintain family resilience depends on effective communication and decision-making with their spouses. The study highlights that career women contribute to family resilience across multiple dimensions, including physical, economic, psychological, and socio-cultural aspects. The division of responsibilities between husband and wife reflects mutual cooperation, guided by principles such as mītsāqan ghalīẓan, zawāj, mu’āsharah bil ma’rūf, mushāwarah, and tarāḍin min humaā. These principles align with the fulfillment of the eight core family functions, reinforcing family stability and well-being.